Fostering Design Thinking Competence in High School Students Through STEAM Robotics Lessons Focused on Environmental Protection - Quynh, Le Thi Thuy; Trung, Ta Thanh; Nga, Nguyen Thanh (VNU Journal of Science: Education Research, 2026)
STEAM education is an integrated teaching model that is gaining attention in many countries worldwide. Among the various forms of STEAM education, several studies have documented the positive impact of STEAM robotics education on students' knowledge, skills, and engagement. Environmental issues create a pressing need to educate students to develop problem-solving thinking skills to tackle these challenges through STEAM/STEAM robotics lessons. Environmental protection education is a frequently incorporated topic in STEAM-related subjects at the upper secondary level. However, the current research gap lies in the lack of experimental studies measuring the impact of STEAM robotics on students' design thinking competence, particularly in the context of environmental education. Additionally, designing highly integrated STEAM robotics lessons remains a challenge for high school teachers, requiring a flexible combination of scientific content, technology, and innovative teaching methodologies. This paper provides an overview of environmental protection education content in the upper secondary school curriculum (grades 10, 11, and 12) under the 2018 General Education Program. It specifically focuses on developing and experimentally implementing a STEAM robotics lesson linked to the topic "Physics and Environmental Protection Education" for grade 10 students. We design the lesson based on the design thinking process, which integrates robotics product design and development to enhance students' design thinking competence. The study employs a pedagogical experimental method with a sample of 42 students, including a detailed evaluation of six cases. The experimental results for grade 10 students indicate that the developed STEAM robotics lesson framework is feasible, providing opportunities for students to demonstrate nine behavioural indicators associated with key components: i) Empathy-based problem setting, ii) Ideation; and iii) Modelling. These findings illustrate a positive development in design thinking competence. The study not only shows that STEAM robotics has an effect on environmental education, but it also suggests an effective integrated teaching model that can help improve the quality of STEM education and students' ability to solve problems in the real world.